Comparative analysis of gingival tissue antigen presentation pathways in ageing and periodontitis. (7th January 2014) - Gonzalez, Octavio A.; Novak, Michael J.; Kirakodu, Sreenatha; Orraca, Luis; Chen, Kuey‐Chu; Stromberg, Arny; Gonzalez‐Martinez, Janis; Ebersole, Jeffrey L.
Abstract Aim Gingival tissues of periodontitis lesions contribute to local elevations in mediators, including both specific T cell and antibody immune responses to oral bacterial antigens. Thus, antigen processing and presentation activities must exist in these tissues to link antigen‐presenting cells with adaptive immunity. We hypothesized that alterations in the transcriptome of antigen processing and presentation genes occur in ageing gingival tissues and that periodontitis enhances these differences reflecting tissues less capable of immune resistance to oral pathogens. Materials and methods Rhesus monkeys (n = 34) from 3 to 23 years of age were examined. A buccal gingival sample from healthy or periodontitis sites was obtained, total RNA isolated, and microarray analysis was used to describe the transcriptome. Results The results demonstrated increased transcription of genes related to the MHC class II and negative regulation of NK cells with ageing in healthy gingival tissues. In contrast, both adult and ageing periodontitis tissues showed decreased transcription of genes for MHC class II antigens, coincident with up‐regulation of MHC class I‐associated genes. Conclusion These transcriptional changes suggest a response of healthy ageing tissues through the class II pathway (i.e. endocytosed antigens) and altered responses in periodontitis that could reflect host‐associated self‐antigens or targeting cytosolic intracellular microbial pathogens.